Malnutrition of Under-Five Children: Evidence from Bangladesh - Siddiqi, Md. Nure Alam; Haque, Md. Nuruzzaman; Goni, Md. Abdul (Asian Journal of Medical Sciences, 2011)
Objective: The objectives of this study are to describe the differentials and associated risk factors of malnutrition among under-five children in Bangladesh. Material & Methods: The data extracted from Bangladesh Demographic and Health Survey (BDHS)-2007. Basic anthropometric variables were used for finding prevalence of anthropometric indices (stunting, wasting and under weight) to assess child’s nutritional statuses. Chi- Square test and Logistic Regression technique were used to find out the significant factors associated with child’s nutritional status. Results: The study results showed the high prevalence of stunting and underweight, for instance 42% and 40% of under-five children were stunted and underweighted respectively. The analyses of the study also revealed that household economic status, mother’s education, father’s education, mother’s antenatal visit (s), mother’s age at birth and mother’s BMI are the most significant factor /determinant s of child’s malnutrition. Conclusion: The magnitude of the Child’s malnutrition still is of great concern in Bangladesh. Significant association between maternal related factors and child’s nutritional status has been found in this study. For improving the nutritional status of children or for getting healthy babies the intervention program(s) must connect not only children but also newly mothers and prospective mothers. Key Words: Anthropometric measurement; Malnutrition; Stunting; Underweight; Wasting DOI: http://dx.doi.org/10.3126/ajms.v2i2.3662 Asian Journal of Medical Sciences 2 (2011) 113-119